Income distribution and economic growth in South Africa - Spandau, Arnt Michael Karl Max (Rhodes University, Faculty of Commerce, Rhodes Business School, 1972)
It is the purpose of this study to examine the interplay of supply and demand factors for the South African economy, and to relate this to the functional, personal, and racial distribution of incomes. On the one hand, it appears that a concentration of incomes in the hands of those who possess both the ability and willingness to save, and to utilize the savings for productive investments, is a crucial determinant for the enhancement of economic growth. On the other hand, an excessive income concentration may severely limit the purchasing power of the major part of the population, thus inhibiting domestic investment. The study is developed, partly in terms of a theory of economic development, and partly in terms of a theory of economic growth. The analysis covers the period from 1918 to the present time. Periods during which the actual economic growth would have been faster had the distribution of incomes favoured work income receivers at the expense of other income receivers, are identified by employing a short-term post-Keynesian model of functional income distribution. Periods during which an acceleration of economic growth would have been achieved had the opposite condition prevailed, are also shown. An analysis is made both of the division by race of aggregate income, and of racial wage differentials in particular economic sectors. A noticeable identity between the economic growth performance and racial wage differentials is evidenced both for the mining and manufacturing sectors. It appears that in the long-term, there is regularity in respect of correlations between measures of the inequality in the size distribution of income on the one hand, and the rates of investment and economic growth on the other. From this observation, it becomes evident that inequality in the distribution of personal income has been a necessary condition for the attainment of economic growth in South Africa. It is obvious that a study of this sort necessitates the use of much statistical data. In order to avoid major disturbances in the flow of the theoretical and analytical arguments through the discussion of the statistical material, the work is submitted in two volumes, viz.,Volume 1 dealing with the Theory and Analysis, and Volume II with the Statistical Foundations.
Keywords: Uncatalogued